KARAKTERISTIK UJI PROPERTIS DAN CAMPURAN BETON NORMAL - Pratika Riris Putrianti; Agustinus Agus Setiawan (Jurnal Riset Rekayasa Sipil, 2021)
Normal concrete is another building material that is most widely used in the construction industry. Concrete is meant by reinforcing steel (wire, woven wire) in the concrete cross-section to improve tensile and flexural resistance. The concrete section transfers tensile stress to the reinforcing steel section, which has better tensile strength. Polymer materials that are more resistant to rust can also be used as reinforcement materials. Basically, concrete is made from a mixture of aggregates (fine and coarse), cement, water, and additives. In a concrete mix, the fine and coarse aggregates are bound to the cement matrix. The cement reaction between water and minerals in cement produces a strong matrix, holds the aggregate in place and gives the concrete compressive strength properties. In the current industrial era, material selection for a normal concrete feasibility test is quite challenging due to finding quality materials. Through a series of material feasibility tests for normal concrete mixtures, it is hoped that quality control will be in the use of superior materials. This research was conducted at the Laboratory of PT Jaya Beton Indonesia. Based on the properties test data on the aggregate and concrete materials, it can be concluded that the aggregate materials have met the specifications of the Indonesian National Standard and IJASE. So that the material can be used in the normal concrete mix plan stage (job mix formula) regarding the provisions of the grain gradation using the normal concrete manufacturing method listed in SNI 7656 of 2012 concerning Procedures for Making Normal Concrete. From the results of the trial mix of concrete in Table 20, the authors decided to use the concrete quality f'c 30 MPa with consideration of the effects of the compressive strength of the concrete being relatively stable in terms of deviation.Keywords: test aggregate properties, normal concrete aggregates, material characteristics, concrete mix